Advances in C(sp(2))-H/C(sp(2))-H oxidative coupling of (Hetero)arenes using 3d transition metal catalysts - Bansal, Sadhna; Shabade, Anand B.; Punji, Benudhar (Advanced Synthesis & Catalysis, 2021)
C-H/C-H oxidative coupling has emerged as a straightforward and powerful technique for the construction of (hetero)biaryls, with substantial application to drug discovery, agrochemicals, biology, and material sciences. Mainly aryl-aryl, aryl-heteroaryl, and heteroaryl-heteroaryl couplings via double C(sp(2))-H activation using 4d or 5d noble transition metal catalysts have been extensively studied. Considering the earth-abundant and inexpensive nature of 3d transition metals, the sustainable development of C(sp(2))-H/C(sp(2))-H oxidative coupling employing such metal catalysts has gained significant attention. In this review, we present a comprehensive overview of C(sp(2))-H/C(sp(2))-H oxidative coupling of (hetero)arenes catalyzed by 3d transition metals.
Keywords: (hetero)biaryls; 3d transition metal; Biaryls; C-H activation; cross-dehydrogenative coupling

Chemodivergent coupling of azoarenes with benzyl alcohols via a borrowing hydrogen strategy using a well-defined nickel catalyst - Bansal, Sadhna; Gonnade, Rajesh G.; Punji, Benudhar (Catalysis Science & Technology, 2023)
Chemodivergent (de)hydrogenative coupling of azoarenes with benzyl alcohols is achieved via the N=N bond activation using an inexpensive and well-defined (6-OH-bpy)NiCl2 catalyst. This protocol highlights the construction of C-N bonds via a borrowing hydrogen strategy that offers substituted imines and amines. A range of azo compounds couple with various substituted benzyl alcohols in a tandem hydrogenation/dehydrogenation process. The nickel catalyst along with the K2CO3 or (KOBu)-Bu-t base governed the selectivity in imine and amine formation. A preliminary mechanistic study establishes the crucial role of metal-ligand cooperation (MLC) comprising the distinct radical pathways.

Chemodivergent dehydrogenative coupling of alcohols by 3d metal catalysts - Bansal, Sadhna; Punji, Benudhar (ChemCatChem, 2024)
Chemodivergent synthesis by transition metal catalysts is a straightforward and sustainable approach to achieving valuable organic compounds. Especially, the chemodivergent dehydrogenative couplings of alcohols with organic motifs to develop various saturated and unsaturated compounds are highly environmentally benign due to the reduced waste generation. In this concept review, we presented the 3d transition metal (Mn, Fe, Co, and Ni)-catalyzed chemodivergent synthesis of imines and amines, saturated and unsaturated carbonyl/alcohol compounds, saturated and unsaturated nitriles, N-heterocycles, and N-/C-alkylated indoles. The discussed reaction commanded two or three different products with high chemoselectivity by changing specific reaction parameters, but keeping the catalyst unchanged. Generally, the acceptorless dehydrogenative coupling (ADC) provides unsaturated moieties, whereas the borrowing-hydrogen (BH) process results in saturated compounds. Text for Table of Contents: An overview of the chemodivergent dehydrogenative coupling of alcohols by the Earth-abundant transition metal catalysts is discussed. image
Keywords: 3d metals; Alcohols; chemodivergent; dehydrogenative coupling; heterocycles

Nickel-catalyzed chemodivergent coupling of alcohols: efficient routes to access α,α-disubstituted ketones and α-substituted chalcones - Bansal, Sadhna; Punji, Benudhar (Chemistry- a european journal, 2024)
Chemodivergent (de)hydrogenative coupling of primary and secondary alcohols is achieved utilizing an inexpensive nickel catalyst, (6-OH-bpy)NiCl2. This protocol demonstrates the synthesis of branched carbonyl compounds, alpha,alpha-disubstituted ketones, and alpha-substituted chalcones via borrowing hydrogen strategy and acceptorless dehydrogenative coupling, respectively. A wide range of aryl-based secondary alcohols are coupled with various primary alcohols in this tandem dehydrogenation/hydrogenation reaction. The nickel catalyst, along with KOtBu or K2CO3, governed the selectivity for the formation of branched saturated ketones or chalcones. A preliminary mechanistic investigation confirms the reversible dehydrogenation of alcohols to carbonyls via metal-ligand cooperation (MLC) and the involvement of radical intermediates during the reaction. The chemodivergent nickel-catalyzed approach provides alpha,alpha-disubstituted ketones from aryl-substituted secondary alcohols and benzyl alcohols via the borrowing hydrogen (BH) strategy in the presence of KOtBu, whereas exclusively alpha-substituted chalcones were accomplished in the presence of mild base K2CO3 through an acceptorless dehydrogenative coupling (ADC) strategy. image
Keywords: Alcohols; dehydrogenative coupling; Metal-ligand cooperation; Nickel; substituted carbonyl compounds